FEATURES OF THE IMMUNE RESPONSE AND EFFICACY IMMUNOTHERAPY FOR ROTAVIRUS INFECTION IN CHILDREN - S. G. Gorbunov; L. N. Mazankova; I. D. Maykova; O. I. Demina; E. P. Koval (Детские инфекции (Москва))
The article reflects the changes in both cellular and humoral immunity in rotavirus infection, as well as the correlation between the degree of severity of immunological disorders and the peculiarities of the clinical course of the disease in childhood.  The most significant changes in cytokine status are associated with an increase in interleukin-1b, which is a marker of intoxication. In addition, during rotavirus infection in children reduced the level of induced interferon a and у, that justified the application of a2b-interferon that is part of the drug VIFERON®, containing also vitamins E and C. The appointment of drug VIFERON®, along with basic therapy, including the probiotic strains LGG and ВВ12 in the complex of therapeutic measures  in children with rotavirus infection allows to improve the dynamics of clinical and immunological indicators, as well as to reduce 1.5 times the number of cases of ARI within 6 months of the follow-up observations after the acute period of the disease.